FENOMENA FLYPAPER EFFECT ATAS BELANJA DAERAH PEMERINTAH KABUPATEN/KOTA PROVINSI ACEH TAHUN 2016 - 2020 - Anissa Mutiara Dewi, (2023)
The main objective of the quantitative research is to get answers from the actual occurrence of the flypaper effect on district/city government regional spending in Aceh Province. In this case, secondary data collected through BPS Aceh was used regarding PAD, DAU, DAK, DBH, and regional spending in 2016 - 2020. Panel data regression as a reference for analysis with a total sample of 115 Obs. The study findings show that DAU, DAK, and DBH cause a flypaper effect on regional spending. This research also shows that the regional spending of all districts/cities in Aceh is significantly influenced by PAD, DAU, DAK, and DBH.